The Very Long Chain Fatty Acid (C26:25OH) Linked to the Lipid A Is Important for the Fitness of the Photosynthetic Bradyrhizobium Strain ORS278 and the Establishment of a Successful Symbiosis with Aeschynomene Legumes - Busset, Nicolas; Di Lorenzo, Flaviana; Palmigiano, Angelo; Sturiale, Luisa; Gressent, Frederic; Fardoux, Joël; Gully, Djamel; Chaintreuil, Clémence; Molinaro, Antonio; Silipo, Alba; Giraud, Eric (Frontiers in Microbiology, 2017)
In rhizobium strains, the lipid A is modified by the addition of a very long-chain fatty acid (VLCFA) shown to play an important role in rigidification of the outer membrane, thereby facilitating their dual life cycle, outside and inside the plant. In Bradyrhizobium strains, the lipid A is more complex with the presence of at least two VLCFAs, one covalently linked to a hopanoid molecule, but the importance of these modifications is not well-understood. In this study, we identified a cluster of VLCFA genes in the photosynthetic Bradyrhizobium strain ORS278, which nodulates Aeschynomene plants in a Nod factor-independent process. We tried to mutate the different genes of the VLCFA gene cluster to prevent the synthesis of the VLCFAs, but only one mutant in the lpxXL gene encoding an acyltransferase was obtained. Structural analysis of the lipid A showed that LpxXL is involved in the transfer of the C26:25OH VLCFA to the lipid A but not in the one of the C30:29OH VLCFA which harbors the hopanoid molecule. Despite maintaining the second VLCFA, the ability of the mutant to cope with various stresses (low pH, high temperature, high osmolarity, and antimicrobial peptides) and to establish an efficient nitrogen-fixing symbiosis was drastically reduced. In parallel, we investigated whether the BRADO0045 gene, which encodes a putative acyltransferase displaying a weak identity with the apo-lipoprotein N-acyltransferase Lnt, could be involved in the transfer of the C30:29OH VLCFA to the lipid A. Although the mutant exhibited phenotypes similar to the lpxXL mutant, no difference in the lipid A structure was observed from that in the wild-type strain, indicating that this gene is not involved in the modification of lipid A. Our results advance our knowledge of the biosynthesis pathway and the role of VLCFAs-modified lipid A in free-living and symbiotic states of Bradyrhizobium strains.